Antibody-drug conjugates for breast cancer - Marmé, Frederik (Oncology research and treatment, 2022)
Background: Despite the advances that have been made to improve conventional chemotherapies, their use is limited by a narrow therapeutic window based on off-target toxicities. Antibody-drug conjugates (ADCs) are composed of an antibody and a toxic payload covalently coupled by a chemical linker. They constitute an elegant means to tackle the limitations of conventional chemotherapeutics by selectively delivering a highly toxic payload directly to target cells and thereby increasing efficacy of the delivered cytotoxic but at the same time limiting systemic exposure and toxicities. As such, they appear inspired by Paul Ehrlich’s concept of a “magic bullet,” which he envisioned as drugs that go directly to their target to attack pathogens but remain harmless in healthy tissues. Summary: The concept of conjugating drugs to antibodies via chemical linkers is not new. As early as in the 1960s, researchers started to investigate such ADCs in animal models and first clinical trials based on mouse antibodies began in the 1980s. Although the concept appears relatively straightforward, ADCs are highly complex molecules, and it took several decades of research and development until the first ADC was approved by the FDA in 2000 and the second followed not until 11 years later. The development of an effective ADC is highly demanding, and each individual component of an ADC must be optimized: the target, the antibody, the linker, and its conjugation chemistry as well as the cytotoxic payload. Today, there are 9 approved ADCs overall and 3 for breast cancer. So, the pace of development seems to pick up with over 100 candidates in various stages of clinical development. Many ADCs of the newest generation are optimized to elicit a so-called bystander effect, to increase efficacy and tackle heterogeneous antigen expression. This approach requires a balancing of efficacy and systemic toxicity. Hence, ADCs based on their complex biology cause relevant toxicities, which are characteristic for each specific compound and may include hematologic toxicities, elevated transaminases, gastrointestinal events, and pneumonitis but also ocular toxicities as well as others many physicians may initially not be very familiar with. Management of the side effects will be key to the successful clinical use of these potent drugs. Key Messages: This review focusses on the clinical experience with ADCs approved in breast cancer as well as promising candidates in late-stage clinical development. We will discuss the mode of action, biology, and composition of ADCs and how each of these crucial components influences their properties and efficacy.
Online veröffentlicht: 16. Dezember 2021
Gesehen am 03.09.2024